Modeling plastic deformation of TWIP steel using cohesive zone and crystal plasticity finite element - Wang Cai; Chaoyang Sun; Hongjia Zhang; Lingyun Qian; Linghui Meng; M.W. Fu (Materials & Design)
In this research, the cohesive zone model-crystal plasticity finite element (CZM-CPFE) method was applied to reveal the influence mechanism of grain boundaries (GBs) and grains on the mechanical properties of fine/ultrafine grained TWIP steels. The reliability and efficiency of this method were verified via corroborating with in-situ SEM tensile tests and EBSD/TEM characterisation. When the average grain size was refined from 8.49 to 0.70 μm, the yield stress increased from 181 to 317 MPa and the ultimate tensile strength from 868 to 1004 MPa with little loss of UE, which was successfully predicted by the CZM-CPFE method. Also, the neighbouring grain model revealed that stress concentrations are pronounced near GBs with high misorientation angle due to the dislocation motion and twin growth hindered by GBs. Furthermore, the simulation and experimental results indicated that the critical resolved shear stress (CRSS) for twinning increased to 202 MPa for average grain size reduction to 0.70 μm, which was much higher than the 138.5 MPa for slip, making twin activation more difficult. The application of this work in steels with moderate grain sizes can facilitate understanding of the evolution of the slip and twins and the strain hardening.